Solve it please. "?"

enter image source here

2 Answers
Apr 13, 2018

{(m ddot x_1 + k(x_1-x_2) = -F),(2m ddot x_2 + k(x_2-x_1) = 2 F):}

Applying the Laplace transform

{((s^2+k/m)X_1-k/mX_2=-1/mF+dot x_1(0)+s x_1(0)), (-k/(2m)X_1+(s^2+k/(2m))X_2 = 1/(2m)F+dot x_2(0)+s x_2(0)):}

Now assuming

dot x_1(0) = -u
dot x_2(0) = 2 u

x_1(0)=x_2(0) = 0

((s^2+k/m,-k/m),(-k/(2m),s^2+k/(2m)))((X_1),(X_2)) = ((-1/mF-u),(1/(2m)F + 2u))

and after the anti transformation gives

{(x_1 = u t - sqrt(2/(3km))(F+2m u)sin(sqrt((3k)/(2m))t)),(x_2 = u t + sqrt(1/(6km))(F+2m u)sin(sqrt((3k)/(2m))t)):}

hence

x_2-x_1 = (sqrt(1/(6km))+sqrt(2/(3km)))(F+2m u)sin(sqrt((3k)/(2m))t)

The conclusions are left to the reader.

Apr 13, 2018

xi_(max) =sqrt((16 F^2)/(9 k^2) + (6 m u^2)/(k) ) + (4 F)/(3 k)

Explanation:

For spring extension is xi = x_B - x_A, Newton's 2nd Law applied to blocks is:

Block A: qquad k xi - F = m ddot x_A

Block B: qquad 2F - k xi = 2m ddot x_B

Newton's Law for the system (ignoring spring as it is in the system):

2F - F = (m_A + m_B) ddot x_(cm) implies F = 3m ddot x_(cm) qquad triangle

Centre of mass of system:

x_(cm) = (m_A x_A + m_Bx_B)/(m_A + m_B) = 1/3x_A + 2/3 x_B, so:

....so:

((xi),(x_(cm))) = ((-1,1),(1/3,2/3)) ((x_A),(x_B))

Inverting this:

((x_A),(x_B)) = ((-2/3,1),(1/3,1)) ((xi),(x_(cm)))

and

((ddot x_A),(ddot x_B)) = ((-2/3,1),(1/3,1)) ((ddot xi),(ddot x_(cm)))

Our equations for A& B become:

Block A: qquad k xi - F = m ddot x_(cm) - 2/3 m ddot xi

Block B: qquad 2F - k xi = 2m ddot x_(cm) + 2/3 m ddot xi

We can eliminate x_(cm) using triangle:

Block A: qquad k xi - F = F/3 - 2/3 m ddot xi

implies ddot xi + (3k)/(2m) xi = 2 F/m

This solves as:

xi(t) = alpha sin(omega t) + beta cos(omega t) + (4 F)/(3 k) with omega = sqrt( (3k)/(2m))

xi(0) = 0 implies beta = -(4 F)/(3 k)

xi' = alpha omega cos(omega t) - beta omega sin(omega t )

xi'(0) = 3u implies alpha omega = 3u

implies xi(t) = (3u)/omega sin(omega t) -(4 F)/(3 k) cos(omega t) + (4 F)/(3 k)

=Gamma( ((3u)/omega)/Gamma sin(omega t) -((4 F)/(3 k) )/Gamma cos(omega t)) + (4 F)/(3 k)

where Gamma = sqrt(((3u)/omega)^2 + ((4 F)/(3 k) )^2) = sqrt(16 F^2 ω^2 + 81 k^2 u^2)/(3k omega)

=sqrt(16 F^2 ω^2 + 81 k^2 u^2)/(3k omega) sin(omega t - phi) + (4 F)/(3 k)

EDIT: Now omega^2 = (3k)/(2m) so this simplifies further to:

=sqrt((16 F^2)/(9 k^2) + (6 m u^2)/(k) ) sin(omega t - phi) + (4 F)/(3 k)

Max Extension is therefore:

xi_(max) =sqrt((16 F^2)/(9 k^2) + (6 m u^2)/(k) ) + (4 F)/(3 k)